Vytautas Gužas – Personality and Fate in the History of Lithuanian Partisan Resistance: The Activities and Significance of the Partisan Vytautas Gužas in the History of the Lithuanian Partisan War - Staveckaitė-Notari, Ramona (Genocidas ir rezistencija, 2025)
This article provides a systematic analysis of the biography of Vytautas Gužas (code name: Kardas), who was one of the signatories of the 16 February 1949 Declaration of the Union of Lithuanian Freedom Fighters (ULFF). Archival documents and partisan memoirs are used to reconstruct the trajectory of Gužas’s life and activities, from interwar Lithuania to the culmination of the partisan resistance. The article is meant not only to present biographical facts about the signatory, but also to illuminate the social and cultural context of independent Lithuania that shaped Gužas’s world view and political convictions, which influenced his value-based choices in the face of the Soviet and Nazi occupations. Vytautas Gužas is portrayed as a representative of the patriotic generation of interwar Lithuania.